Implementation of village empower program in supporting form of institutions of village business institutions (BUMDes) (Study on Dayang Suri Village Bungaraya Sub District Siak Regency Riau Province) - Wasiah Sufi; Trio Saputra (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2017)
The purpose of this research is to investigate the implementation of village empowerment program in support of institutional formation of Village Owned Enterprise (BUMDes). The research carried out at Dayang Suri Village, Bungaraya Subdistrict, Siak Regency at UED-SP Karya Bersama. The data used consist of secondary data in the form of documents relating to the implementation of village empowerment program in support of the formation of BUMDes and primary data in the form of direct observation of research location and interview with key informant. Data analysis employed in descriptively qualitative. Based on the result, it mentioned that into the preparation stage, implementation and principles of management of UED-SP Karya Bersama program has been relatively good. However, there are still less maximal aspects such as lack of socialization conducted by village government, lack of transparency or clarity of information by village fund managers and lack of village facilitators as facilitators in decision making. Keywords: poverty, community empowerment, savings and loans, transparency